IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL TO IMPROVE ELEMENTARY SCHOOL STUDENTS' SCIENCE LEARNING OUTCOMES - retno wati; Armi Yuneti (Teaching and General Education Studies, 2026)
Low science learning outcomes among fifth-grade students indicate the need for more effective, student-centered learning models. This study aimed to examine the effectiveness of the Guided Inquiry learning model in improving science learning outcomes of fifth-grade students at SD Negeri 1 Lubuklinggau. The subjects of this study were 22 fifth-grade students. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation sheets, achievement tests, and documentation, and analyzed quantitatively. The results revealed a significant improvement in students’ learning outcomes. Learning mastery increased from 9% in the pre-action stage to 40% in Cycle I after the implementation of Guided Inquiry. Further improvement was achieved in Cycle II, with mastery reaching 86.37%. These findings indicate that the Guided Inquiry learning model effectively enhances students’ understanding of science concepts. In conclusion, Guided Inquiry is a suitable instructional approach for elementary science learning. This study contributes practical evidence for teachers to apply inquiry-based learning to improve science learning outcomes in elementary schools.